A study on the stages of tooth calcification among identical twins in selected schools in Metro Manila - Go, Elizabeth T.
Differences in the stages of tooth calcification are evident when comparing children of the same age and sex. Would this observation hold true when comparing identical twins? Results of this study showed that there are no significant differences in the stages of tooth calcification among identical twins. Hopefully, this pilot study will encourage researchers to further explore the phenomenon of identical twins and their significance in the field of dentistry.